PERAN ROLE STRESS DALAM MEMEDIASI PENGARUH BEBAN KERJA TERHADAP BURNOUT PERAWAT - Suardiningsih, Nana; Ketut Surya, Ida Bagus (E-Jurnal Manajemen, 2021)
Burnout syndrome is a physical, psychological, and mental symptom that is destructive that results from doing monotonous work and pressing continuously. The purpose of this study was to explain the effect of workload on burnout, explain the effect of role stress on burnout, explain the effect of workload on role stress, and explain the use of role stress to mediate workload on burnout. This research was conducted at Tk II Udayana Hospital Denpasar. The number of samples used in this study amounted to 68 nurses who were determined by the non-probability sampling technique, that is saturated sample method. The data analysis technique in this research is path analysis. The results of this study found that workload has a positive and significant effect on burnout. Role stress has a positive and significant effect on burnout. Workload has a positive and significant effect on role stress. Role Stress mediates the effect of workload on burnout. Keywords : role stress, workload , burnout